Generation of a human induced pluripotent stem cell (iPSC) line ERPLi004-A from an Alpha-1 antitrypsin deficiency (AATD) patient with SERPINA1 mutation - Harshini Surendran; Rajani Battu; Renjitha Gopurappilly; Chethala N. Vishnuprasad; Rajarshi Pal (Stem Cell Research)
Alpha-1 antitrypsin deficiency (AATD) is an autosomal disorder that causes liver and lung disease. The risk of developing lung emphysema, chronic obstructive pulmonary disorder and liver cirrhosis is observed in >75 % people affected with a homozygous mutation. Here, we describe the generation of an induced pluripotent stem cell (iPSC) line from peripheral blood mononuclear cells (PBMC) isolated from a AATD patient using non viral and non-integrating episomal vectors. The iPSC line expresses pluripotency markers, generates three germ layers in vitro and retains a normal karyotype (P20) and can provide an ideal tool for disease modelling, drug screening, and personalized medicine.